Public Challenges and Employee Performance: An Analysis of the Roles of Organizational Adaptation and Human Resource Management Innovation at the Medan City Regional Financial and Asset Management Agency (BKAD) - Chatrin Amelia Gurusinga; Jhon Sehatdo Natanael Saragih; Muhammad Permana Yoga; Luter Girsang (SEAN Institute, 2026)
This study seeks to examine the impact of public problems, organisational adaptation, and innovations in HR management on employee performance within the BKAD of the Medan Mayor's Office. This research employs a quantitative methodology including a sample of 94 employees. The sampling technique employs saturated samples, utilising the entire population as the sample. Data acquisition was conducted by interviews, surveys, and documentation. The employed analytical approaches comprised validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination, t-test, and F-test. The findings indicated that societal challenges positively and significantly influenced employee performance, with a significance value of 0.029. Additionally, organisational adaptation positively and significantly affected performance, with a significance value of 0.000, while HR management innovation also had a positive and significant effect, with a significance value of 0.000. Concurrently, public issues, organisational adaptation, and innovations in HR management exert a positive and strong influence on employee performance, evidenced by an Fcal value of 62.033, surpassing the Ftable of 2.710. The adjusted R-squared value of 0.663 signifies that 66.3% of the variance in employee performance is attributable to the three independent variables, and the remaining 33.7% is accounted for by external factors not included in the study. The research findings indicate that public problems, organisational adaptation, and innovation in human resource management positively and significantly impact employee performance at the BKAD of the Medan Mayor's Office.